Efek Informasi Asimetri Terhadap Kebijakan Dividen - Hadri Kusuma (Jurnal Akuntansi dan Auditing Indonesia, 2006)
This research examines the influence of asymmetric information on dividend policy using an alternative explanation of pecking order theory for a sample of manufacturing firms listed on the Jakarta Stock Exchange between 2000 and 2004. The result of the tests indicates that dividends are negatively related to the level of asymmetric information. This finding is consistent with the theory of pecking order but does not provide a support for the signaling theory.Keywords: asymmetric information, dividend, signaling theory, pecking order theory